Optimization of piezoelectric energy harvesting system (2014)
In recent years, piezoelectric generator was chosen as an autonomous solution for powering low power electronic devices because it has the advantages of the simplest setup and flexibility in dimension control as well as the fact that abundant mechanical vibrations are available everywhere. However, the present piezoelectric material generates extremely low power density and this has restricted its use in a wide array of applications. Several optimization techniques, such as DC-DC buck converter, synchronous charge extraction and SSHI techniques, with high conversion efficiency at the intermediate stage were successfully developed. But the results relied on the outcome of piezoelectric power harvested at the initial harvesting stage and the optimization works at this initial stage have seldom been reported so far. The objective of this research work was to develop an efficient piezoelectric power harvesting system to optimize and to further increase its power density output at the initial harvesting stage with the availability of the existing piezoelectric materials. This begins with the selection of the fitting theoretical model for the piezoelectric generator in the form of composite cantilever beam and then validation of the selected model. The work continues with the physical optimization for individual piezoelectric beam and configuration optimization as more than one beam was used. The physical optimization focused the parametric studies on physical properties of the piezoelectric material used. The results showed that the generation of energy can be optimized by increasing the cantilever length, increasing the piezo stress and strain constants as well as lower Young's modulus ratio and higher thickness ratio of the material to its host. The optimization study is then performed on two major configurations which are single active layer and two-active layer. The two-active layer piezoelectric beam further extended to the series and parallel connections. The two-active layer piezoelectric beam in parallel connection gave better performance in terms of harvested energy compared to others. In order to increase these outcomes, a new method is proposed by folding a given piezoelectric material equally and then splitting it for the use of electrical power generation. These reduced-width materials lower the damping effect on the setup but keeping the natural frequency of the system constant, hence the harvesting system becomes more efficient in scavenging energy from vibration. Experimental results showed good agreement with the theoretical expectations. This method can be incorporated into other optimization technique for better result. Moreover, the bandwidth of the harvesting system increased with small modification of the natural frequency of each split material in the system.